Differential insular cortex subregional vulnerability to α‐synuclein pathology in Parkinson's disease and dementia with Lewy bodies - Fathy, Y. Y.; Jonker, A. J.; Oudejans, E.; Jong, F. J. J.; Dam, A.‐M. W.; Rozemuller, A. J. M.; Berg, W. D. J. (Neuropathology and applied neurobiology, 2019)
Aim The insular cortex consists of a heterogenous cytoarchitecture and diverse connections and is thought to integrate autonomic, cognitive, emotional and interoceptive functions to guide behaviour. In Parkinson's disease (PD) and dementia with Lewy bodies (DLB), it reveals α‐synuclein pathology in advanced stages. The aim of this study is to assess the insular cortex cellular and subregional vulnerability to α‐synuclein pathology in well‐characterized PD and DLB subjects. Methods We analysed postmortem insular tissue from 24 donors with incidental Lewy body disease, PD, PD with dementia (PDD), DLB and age‐matched controls. The load and distribution of α‐synuclein pathology and tyrosine hydroxylase (TH) cells were studied throughout the insular subregions. The selective involvement of von Economo neurons (VENs) in the anterior insula and astroglia was assessed in all groups. Results A decreasing gradient of α‐synuclein pathology load from the anterior periallocortical agranular towards the intermediate dysgranular and posterior isocortical granular insular subregions was found. Few VENs revealed α‐synuclein inclusions while astroglial synucleinopathy was a predominant feature in PDD and DLB. TH neurons were predominant in the agranular and dysgranular subregions but did not reveal α‐synuclein inclusions or significant reduction in density in patient groups. Conclusions Our study highlights the vulnerability of the anterior agranular insula to α‐synuclein pathology in PD, PDD and DLB. Whereas VENs and astrocytes were affected in advanced disease stages, insular TH neurons were spared. Owing to the anterior insula's affective, cognitive and autonomic functions, its greater vulnerability to pathology indicates a potential contribution to nonmotor deficits in PD and DLB.